1986
DOI: 10.1128/mcb.6.1.150
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the intracisternal A-particle is elevated during differentiation of embryonal carcinoma cells.

Abstract: Three cDNA clones coding for the 3' region of the intracisternal A-particle (IAP), a mouse endogenous retrovirus, were isolated during screening of a library for genes whose expression was modulated during the retinoic acid-induced differentiation of the embryonal carcinoma cell line F9 into parietal endoderm-like (PE-like) cells. In contrast to previously reported results, no IAP transcripts were detected in either F9 cells or two pluripotent cell lines tested. Instead, IAP transcripts as well as IAPs were ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…In some embryonic carcinoma lines after induction of their differentiation by retinoic acid (RA), a reduction but not a complete elimination of IAP production was observed that paralleled with a reduction in lAP mRNA expression (Hojman-Montes de Oca eta [., 1983). However, in other experiments RA-induced differentiation of embryonal carcinomas resulted in an increase in IAP expression (Howe & Overton, 1986). In BL6 melanoma cells expressing the endogenous or transfected H-2K b gene, loss of lAPs was not associated with an increase in differentiation or loss of malignant properties.…”
Section: Discussionmentioning
confidence: 96%
“…In some embryonic carcinoma lines after induction of their differentiation by retinoic acid (RA), a reduction but not a complete elimination of IAP production was observed that paralleled with a reduction in lAP mRNA expression (Hojman-Montes de Oca eta [., 1983). However, in other experiments RA-induced differentiation of embryonal carcinomas resulted in an increase in IAP expression (Howe & Overton, 1986). In BL6 melanoma cells expressing the endogenous or transfected H-2K b gene, loss of lAPs was not associated with an increase in differentiation or loss of malignant properties.…”
Section: Discussionmentioning
confidence: 96%
“…The transcriptional activation of IAP sequences appears to be under the control of a complex series of regulatory proteins (11)(12)(13)31) and is influenced by such variables as DNA methylation (14,29,35) and the state of cellular differentiation (21) or transformation (1). Activation of cellular genes by local insertion of IAP sequences has been postulated to be due to one of at least three general mechanisms: the introduction of a cis-acting IAP LTR enhancer either 5' (37, 49, 50) or 3' (44,45) to the gene; the more theoretical possibility of separating the promoter of a cellular gene from 5' inhibitory sequences by the intervening insertion of an IAP sequence; and the introduction of an alternative, LTR-encoded promoter 5' to the cellular gene (9,23,37,46,49,50).…”
Section: Discussionmentioning
confidence: 99%
“…In our analyses of the mechanism by which IAP expression becomes activated, we have found that IAP gene expression in murine F9 EC cells, which resemble early embryonic cells, is restricted, whereas upon differentiation of these cells into parietal endoderm-like cells, IAP expression becomes highly activated. IAP expression is also activated in the parietal endoderm cell line PYS-2 (18). Two DNA elements have been identified.…”
mentioning
confidence: 98%